Faktor – faktor yang berhubungan dengan Penurunan Tinggi Fundus Uteri pada Ibu Nifas 6 jam Post Partum - Siti Rofi’ah; Bekti Yuniyanti; Adi Isworo (Jurnal Riset Kesehatan, 2015)
This research aim is to analyze the factors that have correlation with the height of fundus utery to parturition mother after getting post partum 6 hours. The kind of this research is explanatory research by quantitative approach. The population research were all parturition mothers with post partum 6 hours about 60 women in area of Borobudur clinic Magelang regency on August 2013, but the samples that fulfilled the inclusive and exclusive criteria were about 53 people. The analyze used Spearman Rank test, and Wilcoxon test. The research result showed that there was no significant correlation between age, parity, nutrient statues based on haemoglobin and body mass index, early mobilization and initiate breastfeeding with height of fundus uteri post partum 6 hours. Suggested to KIA, Health Department to provide technical guidance and supervise routinely to the midwives in giving midwifery care especially to the post partum mother.